Neoliberal politics and state modernization in Chilean penal evolution - Wilenmann, Javier (Punishment & society, 2020)
Following the general rise of incarceration rates in Latin America, two general frameworks have been influential in attempting to explain the phenomenon: the neoliberal and the state transformation theses. The article takes the case of Chile, the Latin American model of neoliberal governance, to test the broad explanatory power of both frameworks. By doing so, it shows that the connection with a narrative of substitution has distortive potential. Although the Chilean case does show that investment in state capacity augmentation and output maximization mechanisms did have direct effects on incarceration rates, no change in the project of control through criminal justice can be appreciated. Rather than changing its orientation towards the type of social control it provides for, the system still stands for the traditional Latin American project of control of a large, marginalized population through confinement.